Accuracy in the estimation of children's food portion sizes against a food picture book by parents and early educators. (27th December 2018) - Nissinen, Kaija; Korkalo, Liisa; Vepsäläinen, Henna; Mäkiranta, Päivi; Koivusilta, Leena; Roos, Eva; Erkkola, Maijaliisa; ,
Abstract: Validated methodological aids for food quantification are needed for the accurate estimation of food consumption. Our objective was to assess the validity of an age-specific food picture book, which contains commonly eaten foods among Finnish children, for parents and early educators in estimating food portion sizes. The food picture book was developed to assist in portion size estimation when filling in food records in the Increased health and wellbeing in preschools (DAGIS) study. All ninety-five food pictures in the book, each containing three or four different portion sizes, were evaluated at real-time sessions. Altogether, seventy-three parents and 107 early educators or early education students participated. Each participant evaluated twenty-three or twenty-four portions by comparing presented pre-weighed food portions against the corresponding picture from the food picture book. Food portions were not consumed by participants. The total proportion of correct estimations varied from 36 % (cottage cheese) to 100 % (fish fingers). Among the food groups, nearly or over 90 % of the estimations were correct for bread, pastries and main courses ('piece products' such as meatballs and chicken nuggets). Soups, porridges, salads and grated and fresh vegetables were least correctly estimated (<65 % correct estimations). There were small differences in evaluations of berries and fresh fruits, warm vegetables and pastries between the parents and early educators, but other estimations were mostly similar. The children's food picture book was found to be a useful aid for the estimation of food portion sizes. Parents and early educators evaluated the portion sizes with similar accuracy.